Young ICT entrepreneurs provide solutions for agriculture - Oluwadamisi Okunlola, Festus; Adenmusun, Adetola (Technical Centre for Agricultural and Rural Cooperation, 2016)
The IITA Youth Agripreneurs' (IYA) ICT unit has established its own businesses by making use of ICT tools, like drones. The members also give ICT trainings with the aim to enhance agriculture and sensitise rural entrepreneurs.